Strike Now and Ask Questions Later Witchcraft Stories in Ukraine - Kononenko, Natalie (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1998)
Ukrainian witchcraft beliefs, as attested in materials collected by the author and in stories recorded in the early part of this century by Volodymyr Hnatiuk, serve many functions. They alleviate tensions between neighbors over property, especially foodstuffs such as milk, explaining why one villager has more milk than another or why someone suffers a sudden drop in milk production. By providing a vehicle for victim-blaming, especially in failed love relationships, they excuse misbehavior and assuage feelings of guilt. Most strikingly, they provide an excuse for community inaction. There were no witchcraft trials in Ukraine and accusations of witchcraft, instead of preceding persecution of a presumed witch, usually come after an attack and serve to justify the violent behavior of the attacker. When someone commits a violent act, be it a man who feels guilty over jilting his lover and strikes her to punish her for the anger he fears she harbors towards him, or a man, often drunk, who attacks at random, the community chooses to explain the attack rather than to punish it. The explanation is that the victim must have been guilty of witchcraft.